Maternal Perinatal HIV Infection Is Associated With Increased Infectious Morbidity in HIV-exposed Uninfected Infants. Issue 5 (May 2019) - Powis, Kathleen M.; Slogrove, Amy L.; Okorafor, Ibeawuchi; Millen, Lily; Posada, Roberto; Childs, Jocelyn; Abrams, Elaine J.; Sperling, Rhoda S.; Jao, Jennifer
Abstract : Background: The aging population of females with perinatally-acquired HIV (PHIV) are having their own children. HIV-exposed uninfected infants (HEU-N) born to women living with non-perinatally-acquired HIV (NPHIV) experience higher infectious morbidity compared with HIV-unexposed infants (HUU). Little is known about the infectious morbidity risk of HIV-exposed uninfected infants (HEU-P) born to PHIV women. Methods: We evaluated prevalence of infectious cause hospitalizations (ICH) during the first year of life among HEU-P, HEU-N and HUU infants in a United States (U.S) tertiary care center. Maternal HIV status was categorized as PHIV vs. NPHIV vs. HIV-uninfected. Generalized Estimating Equation models were fit to evaluate the association between maternal HIV status and infant ICH. Results: ICH was evaluated among 205 infants, 28 HEU-P infants, 112 HEU-N infants, and 65 HUU infants. PHIV women were younger compared with NPHIV and HIV-uninfected women (median age 22 years vs. 29 and 23 respectively, p <0.01). Overall, 21% of HEU-P, 4% of HEU-N and 12% of HUU infants experienced at least one ICH event ( p <0.01) in the first year of life. After adjusting for confounders, HEU-P infants were at increased ICH risk compared with HEU-N infants [adjusted odds ratio (aOR)=7.45, 95% Confidence Interval (CI):1.58-35.04]. In sub-group analysis of HEU infants, excluding HUU infants, this relationship persisted after adjustment for maternal CD4 and HIV RNA level (aOR=10.24, 95% CI:1.66-63.31) Conclusions: In a small U.S. cohort, HEU-P infants experienced increased ICH risk. Differences in intrauterine environments, social factors, or access to care may be important factors to assess in future larger studies.